Nitrogen‐Doped MoS2 Foam for Fast Sodium Ion Storage. Issue 13 (13th May 2019) - Tao, Peng; He, Junjie; Shen, Tong; Hao, Yu; Yan, Jingkai; Huang, Zijie; Xu, Xueer; Li, Meng; Chen, Yu
Abstract: A novel 3D porous foam consisting of interlinking N‐doped MoS2 nanosheets is synthesized through a templating‐drying‐carbonization process, where melamine‐formaldehyde is used as both template and nitrogen source. Benefit from the N‐containing MoS2, 3D porous structure, and residual N‐doped carbon, N‐doped MoS2 foam (NMF) exhibits greatly improved electrochemical performance especially in term of rate capability for sodium storage compared with their pristine counterpart. Specifically, NMF shows outstanding rate capability with high reversible capacities reaching up to 407 mAh g −1 after 100 cycles under a current density of 1 A g −1, whereas the charge capacity of pristine MoS2 quickly decays to 60 mAh g −1 after 35 cycles at the same current density. In addition, the important role of pseudocapacitive behavior in the high rate sodium storage performances of NMF is investigated by kinetics calculation. The band structure and partial density of states of NMF are calculated in order to further explore the change of electronic structure induced by N atom doping in MoS2 and its correlation with high rate performance. Furthermore, a Na + full‐cell with NMF anode and Na3 V2 (PO4)3 cathode is assembled and successfully powered a 2 V light‐emitting diode lamp. Abstract : A novel 3D foam consisting of interlinking N‐doped MoS2 nanosheets is utilized as anodes in both half‐ and full‐cell sodium ion batteries. Electronic conduction is enhanced by N‐doping in MoS2 which is confirmed by partial density of states calculation. The resultant MoS2 foam exhibits high rate sodium ion storage performance.